Labdane-Type Diterpenes from the Aerial Parts of Rydingia persica: Their Absolute Configurations and Protective Effects on LPS-Induced Inflammation in Keratinocytes - Alilou, Mostafa (J Nat Prod, 2020)
[Image: see text] Phytochemical investigations of an extract of the aerial parts of Rydingia persica led to the isolation of 14 labdane-type diterpenoids, of which compounds 1–5, 8, and 12–14 turned out to be new natural products, while the remaining compounds were isolated for the first time from the genus Rydingia. Their structures were elucidated using 1D- and 2D-NMR and mass spectrometry, and their absolute configurations were determined by quantum chemical calculation methods. Furthermore, DP4+ NMR chemical shift probability calculations were performed for compounds 12–14, in order to elucidate the orientation of the ambiguous chiral center at C-15, prior to absolute configuration determination. The methanol extract of the aerial parts of R. persica along with subfractions obtained and selected isolated compounds were evaluated for their effects on inflammation-related factors such as nitrotyrosine formation, IL-6 release, and TNF-α release, along with tight-junction proteins claudin-1 and occludin expression in LPS-stimulated HaCaT cells. Occludin and claudin-1 are tight-junction proteins, which play a pivotal role in wound repair mechanisms. Overall, the subfractions and compounds isolated showed moderate to high activity, indicating that labdane-type diterpenoids contribute to the anti-inflammatory and wound-healing activity of R. persica.